The institutionalisation of the european security and defence policy - Rákoczy Pedersen, Steen Bonde (2006)
The thesis identifies a rapid development within the European Security and Defence Policy (ESDP) since 1999 and it analyses to what extend the agencies, bodies and units in the framework of ESDP can be said to have caused the development. The theoretical framework is the three directions within new institutionalism: historical institutionalism, rational choice institutionalism, and sociological institutionalism. The aim of the analysis is to determine if the different agencies, bodies and units can exercise influence on the decision makers. The findings are that they do have influence through institutionalised processes. Interviews with different civil servants and military officers support the findings.